Keratinophilic Fungi: Diversity And Abundance in the Soil of Ajmer District, Rajasthan - Jangid Renu; Ojha Shruti (Journal of Fungal Diversity, 2025)
Soil is a natural habitat and ecosystem for microorganisms, including bacteria and fungi. Mostly keratinophilic fungi are found in soil, use keratin as a growth substrate, and are essential to the natural degradation of keratin waste. These fungi include dermatophytes, a potential source of infectious diseases in humans and animals and cause dermatophytosis. One hundred thirty-six soil samples were collected from several sites including animal habitats in Ajmer district, Rajasthan, India. The soil samples were used for the study of keratinophilic fungi related to species richness, abundance, and diversity. The Physio-chemical properties of collected soil samples were analyzed and examined in soil microflora for temperature, pH, and macronutrients including nitrogen, phosphorus, and potassium. Ninety-eight soil samples (72%) showed positive results for the keratinophilic fungal isolates. The isolated fungal species belonging to eight genera and seventeen species included Aspergillus niger, A. flavus, A. fumigatus, Chrysosporium tropicum, Microsporum gypseum, M. canis, Fusarium solani, F. oxysporum, F. verticilloides, Trichophyton mentagrophytes, T. rubrum, T. tonsurans, T. terrestre, T. equinum, Penicillium, Mucor circinelloides, and Blastomyces. The temperature recorded for keratinophilic fungi ranged between 25℃ and 37℃ and pH was found in the range of 7.0 to 8.5. The fungal community was dominated by the order Onygenales followed by Eurotiales and Hypocreales belonging to the phylum Ascomycota.
Keywords: Keratinophilic fungi